ASSESSING THE HEALTH OF REGIONAL DEVELOPMENT BANKS THROUGH CAMELS METHOD - El ISLAMI, MUHAMMAD FATCHULLAH; IKBAL, MUHAMAD (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2024)
Using the CAMELS method, this study aims to compare the health of two regional development banks, Bank Jatim and Bank Jateng. The findings will inform government regulations, internal bank policies, investor decisions, academic literature, and public savings choices. It employs a descriptive quantitative approach, analyzing financial statement data from 2017 to 2021. Bank Jatim demonstrates better health than Bank Jateng, particularly in asset quality, profit margin, liquidity, and market risk sensitivity. However, both banks share similar capital and management qualities. Unlike previous research focusing on large state-owned banks, this study prioritizes regional development banks in East Java and Central Java, aiming to offer insights into their health levels through CAMELS analysis.